Implementation of the Basic Principles of Sharia Economics in Traders' Buying and Selling Transactions at Tolo' Market, Kelara District, Jeneponto Regency - Muthalib, Ahmad Abdul; Zulkifli, Zulkifli; Marunta, Ristiyanti Ahmadul; Anwar, Desy Rahmawati (International Journal on Advanced Science, Education, and Religion, 2025)
Traditional markets are the center of people's economic activities that are not only oriented towards fulfilling material needs, but also loaded with ethical and moral values. In practice, buying and selling transactions in traditional markets are still faced with various problems, such as fraud, lack of transparency, and weak accountability, which have the potential to deviate from the principles of Islamic economics. This study aims to analyze the application of basic principles of sharia economics in buying and selling transactions by traders in Tolo' Market, Kelara District, Jeneponto Regency. This research uses a descriptive qualitative approach with field research methods. Data collection techniques are carried out through observation and interviews with traders and buyers, while data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that in general, traders at Tolo' Market have applied the basic principles of sharia economics, including the principles of justice, transparency, halal, and trust, although the implementation is not fully optimal. The principles of fairness and transparency are quite visible in the pricing and delivery of information on goods, the principle of halal is carried out properly through the selection of halal and consumable goods, and the principle of trust is reflected in the responsibility of traders to buyer complaints. However, the principle of accountability is still a challenge, especially related to the recording of transactions that have not been carried out systematically. This research is expected to be a reference in strengthening sharia business ethics in traditional markets and encouraging increased awareness of traders on the importance of applying sharia economic principles as a whole.